Physical activity for children and young people aged 5-18 years during COVID-19. Stay safe; be active - Fawkner, S.; Niven, A.; Hanson, S.; Williamson, C.; Hanson, C. L. (British Journal of Sports Medicine, 2020)
Covid-19 presents many challenges and anxieties. For parents and carers of school-aged children (young people), daily lives are barely recognisable. We are attempting to juggle work, life and schooling from home, while trying to keep everyone happy. The benefits of physical activity for young people are widely recognised, and during COVID-19, moving more and sitting less is very important to help families maintain physical and mental health. Being confined to home means that young people, who are used to school P.E., after school activities, active travel, organised sport and outdoor play, have to find a `new normal`. Screen use, which is mainly sedentary, has likely increased because of the switch to online education, entertainment and `babysitting` services for overstretched parents.